2015
DOI: 10.1371/journal.pntd.0003656
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic Activity In Vivo of Epiisopiloturine against Juvenile and Adult Worms of Schistosoma mansoni

Abstract: Schistosomiasis is a serious disease currently estimated to affect more that 207 million people worldwide. Due to the intensive use of praziquantel, there is increasing concern about the development of drug-resistant strains. Therefore, it is necessary to search for and investigate new potential schistosomicidal compounds. This work reports the in vivo effect of the alkaloid epiisopiloturine (EPI) against adults and juvenile worms of Schistosoma mansoni. EPI was first purified its thermal behavior and theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…This finding could be attributed to a high reduction in the worm burden as a result of treatment with spironolactone and/or inhibition of oviposition by adult helminths. A significant reduction in eggs collected from the intestine (oogram) or feces has been described with other antischistosomal compounds (21)(22)(23). In addition, the pathology normally associated with the deposition of schistosome eggs in the spleen and liver was clearly ameliorated, mainly when spironolactone was administered for 5 days.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This finding could be attributed to a high reduction in the worm burden as a result of treatment with spironolactone and/or inhibition of oviposition by adult helminths. A significant reduction in eggs collected from the intestine (oogram) or feces has been described with other antischistosomal compounds (21)(22)(23). In addition, the pathology normally associated with the deposition of schistosome eggs in the spleen and liver was clearly ameliorated, mainly when spironolactone was administered for 5 days.…”
Section: Discussionmentioning
confidence: 94%
“…For scanning electron microscopy, control and treated adult parasites were fixed for at least 3 h in 2.5% glutaraldehyde (Sigma) at room temperature. Experimental protocols for scanning electron microscopy were published previously (22,23). Samples were metalized with gold using a Desk II sputter coater (Denton Vacuum LLC, Moorestown, NJ) and then observed using a JEOL SM-6460LV high-resolution scanning electron microscopy (JEOL, Ltd., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding V. brasiliana, the analysis showed the presence of alkaloids, tannins and steroids and/or triterpenes. The presence of alkaloids in both plants is important, given that many articles can be found in the literature that refer to the anthelmintic activity of these compounds [7,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Fabri et al [30] demonstrated that treatment with methanolic extract of M. frigidus avoided increase of liver and spleen weight during S. mansoni infection. Studies with epiisopiloturina alkali at dosage of 40 mg/kg achieved similar results and the effects with higher doses were not satisfactory [27,32]. Treatment with arctiin at concentration of 50 mg/kg had not impact on liver weight, since no statistically significant difference was found when compared with control groups.…”
Section: Discussionmentioning
confidence: 93%